Is Obesity Associated with Lower Mini Mental Test Scores among Elderly? A Cross Sectional Study. Issue 6 (18th August 2022) - İnce, Nezire and Öztürk, Müjgan and Meseri, Reci and Besler, Halit Tanju
Abstract: Objectives: Obesity leads to many chronic diseases and its association with cognitive impairment is controversial. The objective was to investigate the association between obesity, anthropometric measurements and cognitive functions of elderly. Methods: Planned cross-sectionally, community-dwelling Cypriots (aged ≥ 50 years) without any neurological disorders, were included. Cognitive impairment evaluated by Mini Mental State Examination (MMSE) was the dependent variable. Socio-demographic variables, anthropometric measurements and obesity were the independent variables. The data was collected via face-to-face interview. Logistic regression models were constituted to determine the association of anthropometric measurements, obesity and dementia. Results: The mean age of participants ( n = 541) was 60.0 ± 8.7 for women ( n = 377) and 61.5 ± 6.0 years for men ( n = 164). According to MMSE, 26.0% of women and 11.0% of men had mild-dementia, and the rest scored normal. After adjusted for age and sex, each unit increase in BMI (OR: 1.045, 95%CI: 1.008–1.091), Waist to height ratio (WHtR; OR: 1.030, 95%CI: 1.006–1.055) and Mid upper arm circumference (MUAC; OR: 1.077, 95%CI: 1.016–1.141) increases the risk of mild-dementia. When education, employment and smoking were included in the models, significance of anthropometric measurements was diminished and only sex and education were remained significant for all. Conclusion: After controlled for age and sex, increment in anthropometric measurements increased the risk of dementia but when education was taken into consideration, this significant association was diminished showing that sex and education is more predominant in a heterogeneous group in means of education. Thus, for heterogeneous groups it might be better to revise MMSE. To determine the association between obesity and dementia cohort studies with longer follow-up duration with larger samples are needed.